Edukasi Kesehatan Pada Komunitas Pemulung Di Kota Makassar Tahun 2022 - Idris, Fairus Prihatin; Asrina, Andi; Sari, Indah; Marwono, Marwono (Rumah Sakit Ibnu Sina, Makassar, 2022)
The scavenger's residence adjacent to the landfill is very prone to exposure to the output of waste decay gases which can cause health problems. The purpose of this Community Health promotion is to increase the understanding of scavengers about the importance of maintaining health and the use of simple personal protective equipment during scavenging activities. Methods: FGD counseling using flayer and personal protective equipment. Result: The level of economy and knowledge of scavengers who have intervention regarding personal hygiene is still very low. Conclusion: There was an increase in the knowledge of scavengers after health education was carried out.